Factors that contribute to customer dissatisfaction towards MPH Bookstores / Nurfarahazreen Mohd Ali - Mohd Ali, Nurfarahazreen (2014)
The main purpose of this study is to investigate the factors that contribute to customer dissatisfaction towards MPH Bookstores. This topic was chosen because the researcher wanted to know what are the factors that contributed to customer dissatisfaction especially in retail industry. This study involved four factors that will affect customer dissatisfaction towards retailer which are physical aspect, personal interaction, problem solving and finally company policy. Primary data of this study data gathered from distribution of questionnaire. 132 questionnaires represent 200 sample were distributed to respondents among customer at MPH Bookstores in Mid Valley Megamall within five days. All 132 questionnaires managed to collected and have been analysed using SPSS version 19. Five analysis methods were used including frequency distribution, descriptive statistics, reliability, correlations and also multiple regression analysis. For the findings, all independent variables are significant to customer dissatisfaction towards MPH Bookstores because the p value is less than 0.05.